PRIOR KNOWLEDGE PESERTA DIDIK PADA PROBLEM BASED LEARNING - Ivonne Ruth Situmeang (Majalah Ilmiah METHODA, 2018)
Problem-Based Learning a learning method using scenarios that are carefully arranged by integrating various disciplines, based on a learning method theme to initiate and stimulate learning by students using prior knowledge through small discussions facilitated by a tutor. Prior knowledge is cognitive strukturr ability possessed by students before participating in learning, which can describe the readiness of students to receive learning to be delivered. So prior knowledge can facilitate the learning process and direct optimal learning outcomes. How to activate prior knowledge of students in problem based learning by brainstorming, cognitive mapping and know, want, Learn (KWL).